Functional analysis of sepiapterin reductase in Drosophila melanogaster - Kim Kiyoung; Kim Heuijong; Yim Jeongbin (Pteridines, 2015)
Sepiapterin reductase (SR) is a key enzyme involved in the biosynthesis of tetrahydrobiopterin (BH4), an essential cofactor for the synthesis of important biogenic amines, including catecholamines and serotonin. BH4 deficiencies have been implicated in several neurological disorders. Here, we characterized sepiapterin reductase (SR) loss-of-function mutants in Drosophila melanogaster and demonstrated that SR mutations are responsible for hyposensitivity to oxidative stress. Biochemical analysis further revealed that SR activity and BH4 levels in SR mutants were significantly reduced. Furthermore, we showed that the levels of phosphorylated Akt and total Akt protein were increased in SR mutants. Our findings indicate that SR plays an important role in the Akt pathway and that SR mutants will be a valuable tool for investigating the physiological functions of BH4.